Analisis Akhlak Siswa Kelas VII MTs Mualimin UNIVA Medan melalui Pembelajaran PAI - Muhammad Syawal Karo Karo; M. Musa Tarigan; Emeliya Sukma Dara Damanik (Al-Munawwarah : Jurnal Pendidikan Islam, 2022)
This research was conducted in September-October 2022 at MTs Muallimin Univa Medan to find out: 1) How is the PAI learning process for class VII students at MTs Muallimin Univa Medan. 2) How are the morals of students in class VII MTs Muallimin Univa Medan during the PAI process. The use of research methods seen from the type of research that is using qualitative research with a descriptive approach, in the process of collecting data the author uses interactive methods and non-interactive methods. Interactive methods include role observation and interviews, while non-interactive methods include observation and analysis in documents.. The results of the research on the learning process carried out by the PAI subject teacher, the researcher saw that children or students in class VII at MTS Muallimin UNIVA Medan responded well to the learning process carried out by the teacher, meaning an attitude of acceptance or morals possessed by students at school can be said to be good. But indeed there are some students who still cannot respond properly to the learning given by the teacher. Because the researcher also took a sample of Class VII, maybe there are some students who are still carried away from elementary school. The researcher's analysis saw and concluded that 70% of the MTs Muallimin students' morals could be said to have good morals. Thus it needs to be improved, such as providing additional learning for students and applying learning models that can create an atmosphere that can make the transfer of knowledge run smoothly from an educator to students.